Menggagas Penggunaan Difable Profile Assessment Dalam Pembuatan Akta Notaris Sebagai Afirmasi Bagi Penghadap dengan Disabilitas Tak Tampak Akibat Penyakit Kronis - Alya Syafira; Pieter E. Latumeten (CV. Era Digital Nusantara, 2026)
Organ dysfunction is a main feature of disability that is not always easily seen. Unfortunately, the definition of organ dysfunction in Law No. 8 of 2016 on Persons with Disabilities (Law 8/2016) narrows the meaning of disability to visible impairments such as physical, intellectual, motor, and sensory disabilities. Using a doctrinal research method through a comparative and case study approach of Constitutional Court Decision No. 130/PUU-XXIII/2025 and related court rulings, this paper aims to formulate how the use of the disability profile assessment method serves as an affirmative action for individuals with invisible disabilities in the preparation of notarial deeds through two key findings. First, invisible disabilities can impair organ function just as severely as visible disabilities, potentially hindering the fulfillment of the requirements for drafting a deed. Second, the affirmative action provided to parties with invisible disabilities is subjective, based on the party’s medical history. Based on these two findings, affirmative action provided to individuals with invisible disabilities is granted in a proportionate and measured manner according to their condition.